The potency of selected ethnomedicinal plants from East Kalimantan, Indonesia as antidiabetic agents and free-radical scavengers - RICO RAMADHAN; PREECHA PHUWAPRAISIRISAN; RUDIANTO AMIRTA; MUHAMMAD FADIL BAGAS DARMAWAN; KAUTSAR UL-HAQ; IRAWAN WIJAYA KUSUMA; HERY SUWITO; NURLITA ABDULGANI; AHMAD MUKHDLOR; SAPARWADI SAPARWADI (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Ramadhan R, Phuwapraisirisan P, Amirta R, Darmawan MFB, Ul-Haq K, Kusuma IW, Suwito H, Abdulgani N, Mukhdlor A, Saparwadi. 2022. The potency of selected ethnomedicinal plants from East Kalimantan, Indonesia as antidiabetic agents and free-radical scavengers. Biodiversitas 23: 2225-2231. Ten ethnomedicinal plant extracts from East Kalimantan flora, traditionally used to treat blood sugar levels and other diabetes-related diseases, were examined in vitro for their antidiabetic and free radical scavenging activities by inhibiting rat alpha-glucosidase and several free radicals such as DPPH, ABTS, and Nitric oxide respectively. Out of the ten plant species investigated for their antidiabetic activity against maltase and sucrase rat alpha-glucosidase, three exhibited the strongest ?-glucosidaseinhibitory activity with maltose as a substrate, namely extracts of Garcinia nervosa, Syzygium caudatilimbum, and Shorea balangeran with IC50 values of 0.046; 0.037; 0.045 mg/mL. Meanwhile, quercetin as a positive control appeared to have a comparable IC50value. Furthermore, among the ten extracts, Syzygium caudatilimbum, Shorea balangeran, and Ixora javanica showed good inhibition against sucrase rat alpha-glucosidase. Moreover, the antioxidant test showed that the ten methanol extracts of plants from East Kalimantan have an antioxidant activity indicated by IC50values. The present study confirms that the ethnopharmacological use of selected plants from East Kalimantan might have potential as an antidiabetic and natural antioxidant.